Determinants of market participation: Special reference to paddy farmers in verugal division - Suventhiran, K.; Karunaanithy, K. (University of Jaffna, 2020)
The study entitled “Factors Determining Market Participation of Paddy Farmers” in the Verugal Divisional Secretariat, Trincomalee District aims to identify the factors that determine the market participation of paddy farmers in the Verugal area and how they relate to and influence market participation; Market share is determined by the amount that paddy farmers sell in their produce. Questionnaires were provided to 100 paddy farmers on a proportionate basis and the data on latent variables were collected through a 5-point Likert-type scale. The results were obtained through regression analysis and descriptive analysis. Thus, the farmer's monthly income, the farm's size is significant and positively influences at 1% level, whereas the farmer's family members, the distance to the market are negatively and significantly influence at 5% level. Meanwhile, the farmer's level of education and the farmer's age negatively influence market share at a 10% significant level. Market information and farmer credit use have a moderate impact on the paddy farmer's market share, while road infrastructure facilities and output cost have a high impact on the farmer's market share. The lowest impact is on the farmer's livestock income and non-farm income. These have highlighted the nature of paddy farmers' market participation in the Verugal area and the factors that determine them. Therefore, it is best to consider not only the use of Western technology in the process of modernization of paddy.
Keywords: Market share; Paddy farmers; Farm size and monthly income